China and special drawing rights: Towards a better international monetary system - Matthew Harrison; Xiao Geng (Journal of Risk and Financial Management, 2019)
China and the international monetary system need each other. The international monetary system is strained, with crisis just around the corner, yet reform is not on anyone's agenda. Meanwhile China, deeply invested in the current system, faces narrowing options as trading partners question its moves abroad, debt levels rise at home, and its current account moves from surplus to deficit. RMB internationalization might appear to provide a way out, but the policy has its limits and tends to exacerbate rather than relieve tensions. We argue that a tension-reducing solution is at hand to the problems of both the international monetary system and China-IMF-style Special Drawing Rights (SDRs). If in a unilateral initiative China were to make the SDR central to its next phase of capital account opening, China's institutions, corporates and individuals-presently restricted in their access to international currency-would likely embrace it. Begun by China, with support from the international community and Hong Kong, promulgation of the SDR would usher in an era of lower tensions, providing space for development and avoidance of conflict within a reordered monetary system in which China would have a more prominent role.
Keywords: F3; G1; P2; 330; China; Special Drawing Rights (SDRs); international monetary system; RMB internationalization; Belt and Road Initiative; risk management